2011
DOI: 10.1177/0194599811422014
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Voice Therapy and Antireflux Therapy Rapidly Recovers Voice‐Related Symptoms in Laryngopharyngeal Reflux Patients

Abstract: Voice therapy may help to restore reversible mucosal change secondary to acidic reflux, inducing rapid resolution of symptoms and shortening of the treatment period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 18 publications
3
41
0
2
Order By: Relevance
“…The study of Park et al showed a significant improvement of all GRBAS items after 3 months of treatment. These authors defined the significant improvement by the enhancement of ≥ 1 item(s) of the scale, which does not coincide with our statistical approach, limiting our literature comparison [39]. The low scores and the lack of significant improvement of the values of the GRBASI items could be related to a majority of mild and moderate LPR patient profiles composing our cohort.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The study of Park et al showed a significant improvement of all GRBAS items after 3 months of treatment. These authors defined the significant improvement by the enhancement of ≥ 1 item(s) of the scale, which does not coincide with our statistical approach, limiting our literature comparison [39]. The low scores and the lack of significant improvement of the values of the GRBASI items could be related to a majority of mild and moderate LPR patient profiles composing our cohort.…”
Section: Discussionmentioning
confidence: 92%
“…Siupsinkiene et al also reported the interest to use VHI as an outcome of the efficacy of the PPI treatment in LPR patients [36]. At the exception of the study of Park et al, the perceptual voice quality assessments conducted in LPR studies were not blinded [13, 3739]. The study of Park et al showed a significant improvement of all GRBAS items after 3 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In all, there have been eight placebo-controlled trials of PPI 21–28 , one that compared PPI and lifestyle modification 29 , and one comparing PPI alone versus combined PPI and voice therapy. 30 Laryngopharyngeal reflux cases were identified using symptoms or laryngoscopic findings alone in three studies 22, 27, 29 , while the remainder used objective testing (i.e., pH probe). Voice outcomes were assessed by a variety of methods: RSI 27, 30 , non-validated voice symptom scores or diaries.…”
Section: Strength Of Associationmentioning
confidence: 99%
“…30 Laryngopharyngeal reflux cases were identified using symptoms or laryngoscopic findings alone in three studies 22, 27, 29 , while the remainder used objective testing (i.e., pH probe). Voice outcomes were assessed by a variety of methods: RSI 27, 30 , non-validated voice symptom scores or diaries. 2226, 28, 29 , and a validated, LPR quality of life survey.…”
Section: Strength Of Associationmentioning
confidence: 99%
See 1 more Smart Citation